2011
DOI: 10.2169/internalmedicine.50.5349
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Endoscopic Findings and Clinical Severity in Ischemic Colitis

Abstract: Background and Aim The incidence of ischemic colitis (IC) in Japan has been increasing due to the westernization of diet and the aging population. The aim of this study was to evaluate the relationship between endoscopic findings and clinical severity in IC. Methods This retrospective analysis included 106 cases diagnosed with IC that were divided into two groups based on endoscopic findings in the acute stage: redness and erosion (RE) versus longitudinal and circumferential ulcers (LCU). The clinical variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Several risk factors for severe IC and bad prognosis have been described [2,5]. Certain endoscopic findings have been related to severity of IC [11]. Even a validated prognostic scoring model has been developed [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several risk factors for severe IC and bad prognosis have been described [2,5]. Certain endoscopic findings have been related to severity of IC [11]. Even a validated prognostic scoring model has been developed [12].…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion criteria for the final analysis were need of hospitalization, at least 1 day of predefined treatment, complete documentation of all clinical parameters including Charlson comorbidity index [10], total colonoscopy with severity index [11], positive histology, and laboratory tests (full blood count, C-reactive protein [CRP], lac-tate dehydrogenase [LDH], and total serum protein). Also stool testing for pathogens including Clostridium difficile was required.…”
Section: Study Population and Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beppu and colaboratores showed that endoscopic classifications were accurate indicators of severity of ischemic colitis [19].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors consider colonoscopy as the test of choice for the diagnosis of IC; however, lower GI endoscopy is not without risk, especially in patients with severe colitis due to the risk of perforation [11, 13, 14]. For these reasons, imaging tests play an important role in the assessment and management of these patients, especially in acute phase (AP).…”
Section: Introductionmentioning
confidence: 99%